Implications for mental health workforce strategy, professional training and supervision of more widespread adoption of the multi-professional Responsible Clinician role: Results of a qualitative inquiry. (May 2021) - Oates, Jennifer; Burrell, Carole; Ebrahim, Selma; Taylor, John; Veitch, Paul; Brandon, Toby
Abstract: Within mental health legislation in England and Wales the Responsible Clinician for specific patients should be the Approved Clinician with the most appropriate expertise to meet their primary assessment and treatment needs. The study aimed to explore nurse and psychologist perspectives on becoming a Responsible Clinician in the context of their limited uptake of the role and calls for an increase in advanced practice roles within mental health. It comprised a qualitative inquiry in the form of a thematic analysis of 12 semi-structured interviews. Four sub-themes emerged under the theme of 'becoming a Responsible Clinician'. They were: (i) the Responsible Clinician amongst other roles; (ii) developing in the role; (iii) working with psychiatrist colleagues; and (iv) organisational context. Responsible Clinicians were juggling the role with other senior clinical responsibilities, often without a coherent programme of ongoing educational development or organisational support structures. If mental health service provider organisations adopt this extended role more widely then role-specific support and supervision arrangements should be in place as part of a coherent workforce strategy. This is particularly important given the legal and ethical responsibilities of the Responsible Clinician. Highlights: The Responsible Clinician role is yet to be taken up widely by non-medics. Responsible Clinicians balance this role with other clinical and managerial roles. Responsible Clinicians require tailored supervision and peer support.